Relationship between leg muscle explosive power and lay-up shoot ability - I Made Wahyu Pranatha Putra wahyu; Anak Ayu Nyoman Trisna Narta Dewi; Nila Wahyuni; I Made Winarsa Ruma (Physical Therapy Journal of Indonesia, 2024)
Background: Lay-up shoot is one of the basic techniques that a basketball athlete must master to be a winner. The shooting technique involves jumping and dribbling the ball as close as possible into the ring. This study aimed to describe the relationship between leg muscle explosive power and lay-up shoot ability. Methods: This research was a descriptive study with a correlational design that used a total sampling technique that targeted all students who were basketball club members at Public Senior High School 8 Denpasar concerning inclusion and exclusion criteria. A vertical jump test measured leg muscle explosive power, and the lay-up shoot ability was measured by doing a lay-up shoot ten times. Results: The results showed a relationship between leg muscle explosive power and the lay-up shoot ability of the students. Most students have above-average legs, muscle explosive power, and good lay-up shooting skills. The better the leg's muscle explosive power, the better the lay-up shoot ability, which shows that the leg muscle explosive power is positively correlated with the lay-up shoot ability Conclusion: This study found a significant relationship between leg muscle explosive power and ability lay-up shoot students at the basketball club Public Senior High School 8 Denpasar.